INTEGRASI KECERDASAN BUATAN DALAM SISTEM PEMESANAN KAMAR - Purbonegoro, Jordan; Pitanatri, Made Uttari (Program Studi Administrasi Perhotelan, 2024)
This research discusses the integration of artificial intelligence (AI) in hotel room booking systems, highlighting its positive impact on customer experience and operational efficiency. From the customer's perspective, the integration of AI can simplify the booking process, increase responsiveness, and provide personalized services. For the hotel, automation of the reservation process and in-depth analysis through AI algorithms enhances operational efficiency and improves the hotel's reputation as innovative. The economic benefits are evident in cost efficiency, revenue growth, and sustainable business models. However, challenges include initial investment, resistance to change, and customer privacy concerns. Technical aspects emphasize the importance of consistent data collection and transparent privacy policy changes. The study concludes that AI integration presents a significant opportunity, but special attention is required to ensure all stakeholders benefit positively.